2006
DOI: 10.1007/s00264-005-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of minimally invasive total hip arthroplasty on the standard procedure

Abstract: Minimally invasive total hip arthroplasty using a short skin incision is a subject of much debate in the literature. The present study estimates the possible minimal length of the exposure in an unselected patient cohort and compares the lateral mini-incision technique and traditional total hip arthroplasty (THA). One hundred and two patients were divided into three groups according to the type of surgery and length of incision: mini-incision (less than 10 cm) was performed in 38 patients; midi-incision (10-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 19 publications
1
37
1
2
Order By: Relevance
“…Szendrõi et al [55] A major finding reported by the overall meta-analysis was the significantly greater risk of iatrogenic nerve injury during MIS compared to conventional procedures. One suggestion for this is related to retractor position.…”
Section: Discussionmentioning
confidence: 97%
“…Szendrõi et al [55] A major finding reported by the overall meta-analysis was the significantly greater risk of iatrogenic nerve injury during MIS compared to conventional procedures. One suggestion for this is related to retractor position.…”
Section: Discussionmentioning
confidence: 97%
“…Total hip arthroplasty (THA) has been one of the most successful orthopaedic procedures over the past 30 years [30,45]. Recently, the techniques of exposure for THA have undergone great change, allowing surgeons to perform THA through mini-incisions (MI) [17,28].…”
Section: Introductionmentioning
confidence: 99%
“…But the majority of studies report no difference between the two techniques [2, [22][23][24] There is no strong evidence supporting the theory of MIS either being a blood-sparing procedure or causing the same amount of blood loss as traditional surgery. We cannot therefore conclude that a different surgical technique leads to blood sparing.…”
Section: Blood Loss Is Minimizedmentioning
confidence: 97%